2006
DOI: 10.17305/bjbms.2006.3215
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Typhus Exanthematicus in Bosnia and Herzegovina

Abstract: Typhus exanthematicus in Bosnia and Herzegovina held in endemic areas from which especially quickly began spread after 1945. That year, in 1945, one hundred epidemics of typhus fever appeared, with the highest incidence rate in Europe of 215.04 per 1,000. Directions of unique program in the world were to eradicate lice of the body, but also establish monitoring of the recidivism, Brill-Zinsser disease. Since 1971, typhus exanthematicus (classical typhus) hasn't appeared in Bosnia and Herzegovina, so epidemic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For the timeliness to achieve full immunity, literature has studied that it takes appropriately six months to produce adequate protection from full immunity after receiving complete HBV vaccination series (Puvačič et al, 2005). In the present study, only 93 students agreed upon six-month time, whereas most of them did not have an idea about the duration of acquiring HBV antibodies.…”
Section: Complications Of Hepatitis B (Cirrhosis)?mentioning
confidence: 52%
“…For the timeliness to achieve full immunity, literature has studied that it takes appropriately six months to produce adequate protection from full immunity after receiving complete HBV vaccination series (Puvačič et al, 2005). In the present study, only 93 students agreed upon six-month time, whereas most of them did not have an idea about the duration of acquiring HBV antibodies.…”
Section: Complications Of Hepatitis B (Cirrhosis)?mentioning
confidence: 52%
“…Elsir and others in Bosnia and Herzegovina have shown that the persistence of anti-HBs after hepatitis B vaccination >10 IU/l stands at 82.53% on average [17]. The largest incidence of anti-HBs >10 IU/l level was registered among the population of children vaccinated against viral hepatitis B at a rate of 88.89%, followed by health workers at a rate of 79.41%, whilst intravenous drug users show the lowest rate at 64.28% reported by Puvačić, et al, (2005) [18]. and lower than the study conducted in Italy, a sufficiently high HBs-Ab titer level was maintained in about 80% of the study with only 20% of individuals resulting in an anti-HBs antibody titer < 10 IU/L, with a slight prevalence of female workers, men 54%, women 46%, and at 21 years (SD ± 4.9), the largest group of HCWs were nurses 53.5%, whereas medical doctors were 30% and other HCWs were 16.5%, showed that female nurses had higher Abs titers compared to men (73.6% vs. 26.4%) [19].…”
Section: Discussionmentioning
confidence: 99%